-16-5n=-7(-6+8n)+3

Simple and best practice solution for -16-5n=-7(-6+8n)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -16-5n=-7(-6+8n)+3 equation:


Simplifying
-16 + -5n = -7(-6 + 8n) + 3
-16 + -5n = (-6 * -7 + 8n * -7) + 3
-16 + -5n = (42 + -56n) + 3

Reorder the terms:
-16 + -5n = 42 + 3 + -56n

Combine like terms: 42 + 3 = 45
-16 + -5n = 45 + -56n

Solving
-16 + -5n = 45 + -56n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '56n' to each side of the equation.
-16 + -5n + 56n = 45 + -56n + 56n

Combine like terms: -5n + 56n = 51n
-16 + 51n = 45 + -56n + 56n

Combine like terms: -56n + 56n = 0
-16 + 51n = 45 + 0
-16 + 51n = 45

Add '16' to each side of the equation.
-16 + 16 + 51n = 45 + 16

Combine like terms: -16 + 16 = 0
0 + 51n = 45 + 16
51n = 45 + 16

Combine like terms: 45 + 16 = 61
51n = 61

Divide each side by '51'.
n = 1.196078431

Simplifying
n = 1.196078431

See similar equations:

| 35-(x-1)=-7(5-x)+28x | | -8x+-12=-44 | | 6x-9=6(x+7) | | 6/b-1=9/1 | | 6x+36/35x+20/3x+18/7x+4 | | 2(x+3)=8(x-2)-2 | | N-13+6=8 | | -16-5n=(-6+8n)+3 | | 3x-5+2=20 | | -9+12x=75 | | -25+7x-4x=53 | | (4p^-5/p^5)^3 | | x-6=4x+3 | | 4y+17=3y-26 | | 10b-5b=55 | | 6+2p-2=8p+14-4p | | 5x-18=63 | | x/-5=17 | | 7m-77-16m-60=28 | | 2-5y=14 | | 8(t-4)+7t=(3t-3)-12 | | 9+7x=-68 | | 7(h+3)=2(6m+8) | | 1/4x-2/3y=8 | | 10x-(9x-6)=10 | | 1/9*9w | | 3(4z+2)-7=95 | | 4x+3/12+x-3/2=3x+1/4 | | 3/4(2x-6)=1/2x-4 | | 3(5h-12)=9 | | 0=3x^2+4 | | 0=3x^2-900 |

Equations solver categories